Phosphatase activity and its relationship with physical and chemical parameters during vermicomposting of filter cake and cattle manure. (22nd May 2015) - Busato, Jader Galba; Papa, Gabriella; Canellas, Luciano Pasqualoto; Adani, Fabrizio; de Oliveira, Aline Lima; Leão, Tairone Paiva
Abstract: BACKGROUND: Recycling of phosphorus (P) from organic residues (ORs) is important to develop environmentally friendly agriculture. The use of this P source depends on phosphatase enzymes, which can be affected by a chain of parameters during maturation of ORs. In this study the phosphatase activity levels throughout vermicomposting of filter cake (FC) and cattle manure (CM) were correlated with different physical and chemical parameters in an effort to increase the knowledge about recycling of P from ORs. RESULTS: FC presented higher total nitrogen content (TNC), total organic carbon (TOC), humic acid (HA) content, water‐soluble P (WSP), phosphatase activities and nanopore volume than CM during vermicomposting. Decreases in TOC of CM resulted from carbohydrate mineralization, which was not observed for FC. CM showed increased hydrophobic index during vermicomposting while FC showed a slight decrease. CONCLUSION: Phosphatase activities correlated positively with TOC, pH and WSP and negatively with HA content for both vermicomposts. Nanopore volume was negatively correlated with phosphatase activities for FC but not for CM. No correlations between hydrophobicity and phosphatase activities were found for FC. Increased hydrophobicity throughout vermicomposting of CM could be partially associated with decreases in phosphatase levels. © 2015 Society of Chemical Industry